ENTREPRENEURSHIP: INFLUENCE OF ENTREPRENEURSHIP TRAINING COURSES ON ENTREPRENEURIAL BEHAVIOUR OF THE STAFF IN OFFICES OF YOUTH AND SPORTS IN YAZD PROVINCE - Benar Nooshin; Yeganeh Far Nastaran; Entezary Zarej Mostafa; Fallah Mehrabadi Saeid (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The main objective of this study was to analyze the entrepreneurial behaviour of the staff of Offices of Youth and Sports in Yazd province and the influence of entrepreneurial training courses on their behaviour. The population under study were all the staff, a total number of 101 persons, of nine (9) Offices of Youth and Sports in Yazd province. The population for pre-testing was equal to the actual population of the study. In terms of methodology it was a descriptive study and in terms of purpose an applicable one. Instrument for data gathering was a survey questionnaire prepared by the researcher and the validity of which was examined by the professors of the university and approved based on their suggestions and views. It consisted of 55 questions in order to measure and evaluate behavioural characteristics of entrepreneurs (Balanced Risk-taking, Locus of Control, Mental Health, Challenge Seeking, Success Seeking or need for achievement, Dreaming or fantasizing, Activism or pro-active, and Ambiguity Tolerance). The stability of the questionnaire was tested and measured byCronbach Alpha Coefficient which was alfa=0.87. The gathered data were analysed using descriptive statistical methods (Mean, Standard Deviation, Charts/Figures) and deductive (non-parametric) methods (Kolmogorov-Smirnov test, Friedman, Mann-Whitney U, Spearman and Pearson).The results showed that there is a significant and positive relationship between activism, dreaming and risk taking characteristics with challenge seeking; and between achievement seeking, mental health and ambiguity tolerance with locus of control characteristic. On the other hand, ranking the characteristics of entrepreneurial behaviour of staff demonstrated that the highest ranking belongs to dreaming and mental health and the lowest ranking belongs to activism and locus of control. Overall, there is a significant relationship between entrepreneurial behaviour and entrepreneurial training. Based on these results, conducting entrepreneurial courses and workshops for staff of Offices of Youth and Sports is highly recommended.